Humeral Interlocking Intramedullary Nailing without Image Intensifier in a Developing Country - Anipole, Olalekan Akeem; Adesina, Stephen Adesope; Eyesan, Samuel Uwale; Ikem, Innocent Chiedu; Akinwumi, Akinsola Idowu; Bamigboye, Philip Oluyemi; Oyewusi, Oluwafemi Oyewole (Nigerian Journal of Orthopaedics and Trauma, 2020)
Background: Interlocking intramedullary nailing under image intensifier has been a standard approach to surgical treatment of humeral fractures. Aim: We present the outcome of humeral interlocking nailing without image intensifier in a developing country. Materials and Methods: This is a prospective study of consecutive patients with humeral shaft fractures who were treated with Surgical Implant Generation Network interlocking nailing for humeral shaft fractures using an external jig system. They were followed up for at least 6 months if there was no evidence of fracture healing and restoration of functional activities. Data collected were processed with the Statistical Package for the Social Sciences and summarised in percentages and means. Results: Forty‑five patients with 46 humeral shaft fractures were studied, with a mean age and standard deviation of 46 ± 14.6 years and male‑female ratio of 1.8:1. At 3 months, 44 (95.7%) of the patients have had radiographic evidence of fracture healing. Over the same period, 35 (76.1%) of them had achieved shoulder abduction >90°, 37 (80.5%) had achieved painless shoulder flexion‑abduction‑external rotation movement and 42 (91.3%) had achieved full activities of daily living. Conclusion: In a resource‑constrained population where image intensifier is difficult to come by, humeral interlocking intramedullary nailing could still be performed using external jig system with a satisfactory outcome.